(untitled) (Research, Society and Development, 2022)
This study aimed to analyze the pedagogical project and the curricular matrix of teacher education for the teaching of Biological Sciences in three Public Universities in the state of Ceará. This is a documentary and bibliographic analysis, using as main sources the legal guidelines and the Pedagogical Political Project of the course (PPC). The analysis of the curriculum, the menus outlined in the PPC’s allowed us to verify that the Biological Sciences course of the three educational institutions researched, meets most of the basic contents required by the National Curriculum Guidelines. However, the disciplines of Libras; Ethics and Professional Legislation require a greater emphasis on an institution, since these contents have the potential to make academics in addition to quality professionals, better citizens and committed to human rights. Regarding the disciplines that are more directly associated with the teacher’s training for the teaching of science and biology, we verified in the three courses that the hours for supervised internship are the ones that weigh the most. While the subjects of basic contents of pedagogical training have a lower workload. It becomes fundamental discussions and evaluations about the Undergraduate courses in Biological Sciences, and their curricula, enabling the correlation between theory and practice, enhancing the bases of the teaching identity and thus forming a problematizing teacher and with a deeper approximation with the teaching practice.